Electrode material, electrode slurry and electrode plate of lithium iron phosphate battery, preparation method of electrode material, electrode slurry and electrode plate, and lithium iron phosphate battery
By introducing molybdenum carbide as a conductive agent into the electrode material of lithium iron phosphate batteries, the problem of reduced electrochemical performance of lithium iron phosphate batteries in low temperature environments is solved, and better rate performance and energy density are achieved.
Patent Information
- Application Number
- CN202310959586.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
The electrochemical performance of lithium iron phosphate batteries in low-temperature environments has been drastically reduced, unable to meet high power requirements, limiting their application and promotion.
Molybdenum carbide is introduced as a conductive agent in the electrode material to reduce the internal resistance of the electrode sheet, improve the rate performance of lithium iron phosphate batteries at low temperatures, and improve the content of the main electrode material and increase the energy density.
It effectively improves the rate performance of lithium iron phosphate batteries at low temperatures, improves the content and energy density of electrode main materials, and meets the usage needs of more application scenarios.
Smart Images

Figure CN119447294A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and relates to an electrode material, an electrode slurry, an electrode pole piece and a preparation method thereof for a lithium iron phosphate battery, and a lithium iron phosphate battery. Background Art
[0002] Lithium iron phosphate materials have become one of the most promising positive electrode materials for lithium-ion batteries due to their low price, safety, reliability, and stable structure. Lithium iron phosphate batteries have excellent electrochemical properties at room temperature, but as the temperature decreases, the electrochemical properties of lithium iron phosphate batteries decrease sharply, and cannot meet the use requirements in low-temperature environments with high power performance requirements, resulting in restrictions on the application and promotion of lithium iron phosphate batteries in low-temperature environments.
[0003] At present, in the preparation process of lithium iron phosphate positive and negative electrode sheets, small particle superconducting carbon black (SUPER-P, referred to as SP) is often added as a conductive agent (for example, Chinese patent application CN202110711107.7). SP is a commonly used conductive agent, which is cheap and practical. However, for lithium iron phosphate batteries with high rate performance requirements at low temperatures, the conductivity of SP needs to be improved.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In view of the shortcomings and defects of the prior art, the present invention aims to provide an electrode material, electrode slurry, electrode plate and preparation method thereof, and a lithium iron phosphate battery for a lithium iron phosphate battery. By introducing molybdenum carbide as a conductive agent into the electrode material, the internal resistance of the prepared electrode plate can be reduced, and the rate performance of the lithium iron phosphate battery at low temperature can be effectively improved. At the same time, the content of the main electrode material can also be effectively increased, which has a positive effect on improving the energy density of the lithium iron phosphate battery.
[0006] In order to achieve the above purpose, the following technical solutions are adopted:
[0007] The present invention provides an electrode material for a lithium iron phosphate battery, which comprises the following components in terms of mass fraction, calculated based on the mass fraction of the electrode material being 100%:
[0008] Electrode active material 96-98%, binder 1.5-2.5% and conductive agent 0.5-1.5%;
[0009] Wherein, the conductive agent includes molybdenum carbide.
[0010] Further, based on the above technical solution of the present invention, the particle size of the molybdenum carbide is D50=0.5-1.3 μm;
[0011] And / or, the conductive agent further includes at least one of carbon nanotubes, SP or acetylene black.
[0012] Further, based on the above technical solution of the present invention, the method for preparing molybdenum carbide comprises the following steps:
[0013] The ammonium molybdate and the carbon source are mixed to carry out a hydrothermal reaction, and after the reaction is completed, the obtained reaction product is separated into a solid and a liquid, and dried to obtain an intermediate product;
[0014] The intermediate product is calcined under a protective atmosphere to obtain molybdenum carbide.
[0015] Further, based on the above technical solution of the present invention, the carbon source includes at least one of sucrose, glucose or fructose;
[0016] And / or, the mass ratio of the ammonium molybdate to the carbon source is 1:(1-1.03);
[0017] And / or, the temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 10-14 h;
[0018] And / or, the drying temperature is 50-70°C and the drying time is 10-14h;
[0019] And / or, the calcination temperature is 750-850° C., and the calcination time is 4-6 hours.
[0020] Further, based on the above technical solution of the present invention, when the electrode material is a positive electrode material, the electrode active substance includes a lithium iron phosphate active substance, and / or the binder includes PVDF.
[0021] Further, based on the above technical solution of the present invention, when the electrode material is a negative electrode material, the negative electrode active material includes graphite, and / or the binder includes carboxymethyl cellulose and / or styrene-butadiene rubber.
[0022] The present invention also provides an electrode slurry for a lithium iron phosphate battery, comprising the electrode material for the lithium iron phosphate battery and a solvent;
[0023] The solvent includes N-methylpyrrolidone and / or water.
[0024] The present invention also provides an electrode plate for a lithium iron phosphate battery, comprising a current collector and an electrode material layer formed on the surface of the current collector, wherein the electrode material layer is made of the electrode slurry of the lithium iron phosphate battery.
[0025] The present invention also provides a method for preparing the electrode sheet of the lithium iron phosphate battery, comprising the following steps:
[0026] The electrode active material, the binder, the conductive agent and the solvent are mixed to obtain a lithium iron phosphate electrode slurry;
[0027] The lithium iron phosphate electrode slurry is coated on the current collector, and then dried and rolled to obtain the electrode plate.
[0028] The present invention also provides a lithium iron phosphate battery, comprising the electrode material of the lithium iron phosphate battery or the electrode plate of the lithium iron phosphate battery.
[0029] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:
[0030] (1) The present invention provides an electrode material for a lithium iron phosphate battery, comprising an electrode active substance, a binder and a conductive agent, wherein the conductive agent comprises molybdenum carbide, which has excellent electrical conductivity, good thermal stability and mechanical stability, and has a good coordination effect with other components of the electrode material, can reduce the internal resistance of the prepared electrode plate, improve the performance of the plate, and effectively improve the rate performance of the lithium iron phosphate battery at low temperature. At the same time, it can also effectively increase the content of the main electrode material, which has a positive effect on improving the energy density of the lithium iron phosphate battery.
[0031] (2) The present invention also provides an electrode slurry and an electrode plate for a lithium iron phosphate battery, both of which are made of the electrode material of the lithium iron phosphate battery mentioned above. In view of the advantages of the above-mentioned electrode material, the electrode slurry and the electrode plate containing it have the same advantages.
[0032] (3) The present invention provides a method for preparing an electrode plate of a lithium iron phosphate battery. The preparation method is simple to operate, has a stable process, and is suitable for large-scale industrial production.
[0033] (4) The present invention provides a lithium iron phosphate battery, comprising the electrode material or electrode plate of the lithium iron phosphate battery. In view of the advantages of the electrode material or electrode plate, the lithium iron phosphate battery comprising the electrode material or electrode plate has a higher energy density and good rate performance at low temperatures, meeting the use requirements of more application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The DCR test diagram of the lithium iron phosphate battery provided in each embodiment and comparative example of the present invention at 25°C and different SOCs for 10 seconds (s) of discharge;
[0035] Figure 2 A graph showing the discharge capacity of lithium iron phosphate batteries provided in various embodiments and comparative examples of the present invention at different rates at 25°C;
[0036] Figure 3 This is a graph of the discharge capacity of the lithium iron phosphate battery provided in each embodiment and comparative example of the present invention at -20°C and 1C. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0038] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0039] According to a first aspect of the present invention, an electrode material for a lithium iron phosphate battery is provided, which comprises the following components in the following mass fractions, with the mass fraction of the electrode material being 100%:
[0040] Electrode active material 96-98%, binder 1.5-2.5% and conductive agent 0.5-1.5%;
[0041] Wherein, the conductive agent includes molybdenum carbide.
[0042] Specifically, the electrode material provided by the present invention can be divided into positive electrode material and negative electrode material according to different specific application scenarios.
[0043] Similarly, electrode active materials can also be divided into positive electrode active materials and negative electrode active materials. For lithium iron phosphate batteries, the positive electrode active material is usually lithium iron phosphate, and its chemical structure is LiFePO4. The specific preparation of lithium iron phosphate active material can be prepared by conventional preparation methods in the field, for example, first preparing a precursor by a solvent thermal method or a chemical coprecipitation method, and then sintering it. The negative electrode active material usually uses graphite and the like. There are certain restrictions on the amount of electrode active material used. The typical but non-restrictive mass fraction of the electrode active material is 96%, 96.5%, 97%, 97.5% or 98%.
[0044] Unlike the conventional use of SP conductive agent, molybdenum carbide is used as the conductive agent in the present invention. Molybdenum carbide has excellent conductivity, and a small proportion can achieve good conductivity, which helps to improve the energy density of the battery cell. At the same time, it also has good thermal stability and mechanical stability, which helps to improve the performance of the electrode. There are certain restrictions on the amount of conductive agent used. If the amount of conductive agent is too high (higher than 1.5%), it will easily lead to a decrease in the energy density of the battery cell. If the amount of conductive agent is too low (lower than 0.5%), it will easily lead to the inability to obtain good conductivity. Therefore, the typical but non-restrictive mass fraction of the conductive agent is 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4% or 1.5% and the numerical range formed between any two points.
[0045] The binder is generally a polymer compound that adheres the electrode active material to the current collector. Its main function is to bond and maintain the electrode active material, enhance the electronic contact between the active material and the conductive agent and between the active material and the current collector, and better stabilize the structure of the electrode. The binder can be a conventional binder in the field. The typical but non-limiting mass fraction of the binder is 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4% or 2.5% and the numerical range formed between any two points.
[0046] The present invention provides an electrode material for a lithium iron phosphate battery, comprising an electrode active substance, a binder and a conductive agent, wherein the conductive agent comprises molybdenum carbide, which has good electrical conductivity. The good coordination between molybdenum carbide and other components of the electrode material can reduce the internal resistance of the prepared electrode pole piece, effectively improve the rate performance of the lithium iron phosphate battery at low temperature, and effectively increase the content of the main electrode material, which has a positive effect on improving the energy density of the lithium iron phosphate battery.
[0047] The particle size of molybdenum carbide will affect the rate performance of the battery cell, so the particle size of molybdenum carbide is further optimized. As an optional embodiment of the present invention, the particle size D50 of molybdenum carbide is 0.5-1.3 μm. Typical but non-limiting D50 particle sizes of molybdenum carbide are 0.5 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.1 μm, 1.2 μm or 1.3 μm and the numerical range formed between any two points.
[0048] The source of molybdenum carbide is not specifically limited, and it can be purchased commercially or prepared by itself. As an optional embodiment of the present invention, the preparation method of molybdenum carbide includes the following steps;
[0049] The ammonium molybdate and the carbon source are mixed to carry out a hydrothermal reaction, and after the reaction is completed, the obtained reaction product is separated into a solid and a liquid, and dried to obtain an intermediate product;
[0050] The intermediate product is calcined under a protective atmosphere to obtain molybdenum carbide.
[0051] The preparation method has a simple preparation process, and the prepared molybdenum carbide material has a uniform particle size and a particle size at the nanometer level.
[0052] Based on the above-mentioned method for preparing molybdenum carbide, there are further restrictions on the types, amounts and process parameters of each raw material.
[0053] As an optional embodiment of the present invention, the carbon source includes at least one of sucrose, glucose or fructose.
[0054] As an optional embodiment of the present invention, the mass ratio of ammonium molybdate to the carbon source is 1:(1-1.03). A typical but non-limiting mass ratio of ammonium molybdate to the carbon source is 1:1, 1:1.01, 1:1.02 or 1:1.03.
[0055] As an optional embodiment of the present invention, the temperature of the hydrothermal reaction is 170-190°C, and the time of the hydrothermal reaction is 10-14h. Typical but non-limiting temperatures of the hydrothermal reaction are 170°C, 172°C, 175°C, 178°C, 180°C, 182°C, 185°C, 188°C or 190°C, and typical but non-limiting times of the hydrothermal reaction are 10h, 11h, 12h, 13h or 14h.
[0056] As an optional embodiment of the present invention, after the hydrothermal reaction is completed and the obtained reaction product is separated into solid and liquid, the step of washing the solid product obtained by the solid-liquid separation is also included, and the washing liquid used for washing is water.
[0057] As an optional embodiment of the present invention, the drying temperature is 50-70°C, and the drying time is 10-14h. Typical but non-limiting drying temperatures are 50°C, 55°C, 60°C, 65°C or 70°C, and typical but non-limiting drying times are 10h, 11h, 12h, 13h or 14h.
[0058] As an optional embodiment of the present invention, the calcination temperature is 750-850°C, and the calcination time is 4-6h. Typical but non-limiting calcination temperatures are 750°C, 760°C, 780°C, 800°C, 820°C, 840°C or 850°C, and typical but non-limiting calcination times are 4h, 5h or 6h.
[0059] As an optional embodiment of the present invention, the protective atmosphere used during calcination includes argon.
[0060] As an optional embodiment of the present invention, the conductive agent further includes at least one of carbon nanotubes, conductive carbon black SP or acetylene black.
[0061] The use of molybdenum carbide in combination with other conductive agents (such as CNT) can improve the manufacturability and conductivity of the pole piece. When molybdenum carbide is used in combination with other conductive agents, the mass ratio of molybdenum carbide to the other conductive agent is not less than 0.2:1, such as 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.5:1, 3:1, 4:1 or 5:1, etc., preferably (0.5-3):1, more preferably (1-2):1. By further limiting the mass ratio of molybdenum carbide to other conductive agents, it is possible to ensure good conductivity while improving the pole piece performance and the energy density of the battery cell.
[0062] As an optional embodiment of the present invention, when the electrode material is a positive electrode material, the electrode active substance includes a lithium iron phosphate material, preferably a nano-scale spherical lithium iron phosphate material.
[0063] Nanoscale spherical lithium iron phosphate materials have small particle size, large contact area with the electrolyte, and short lithium ion migration distance, which can further improve the power performance and low-temperature performance of lithium iron phosphate batteries.
[0064] As an optional embodiment of the present invention, when the electrode material is a positive electrode material, the binder includes polyvinylidene fluoride (PVDF).
[0065] As an optional embodiment of the present invention, when the electrode material is a negative electrode material, the negative electrode active material includes graphite.
[0066] As an optional embodiment of the present invention, when the electrode material is a negative electrode material, the binder includes carboxymethyl cellulose (CMC) and / or styrene-butadiene rubber (SBR).
[0067] According to a second aspect of the present invention, there is also provided an electrode slurry for a lithium iron phosphate battery, comprising the above-mentioned electrode material for a lithium iron phosphate battery and a solvent;
[0068] Wherein, the solvent includes N-methylpyrrolidone (NMP) and / or water.
[0069] In view of the advantages of the electrode material of the lithium iron phosphate battery mentioned above, the electrode slurry prepared therefrom also has the same advantages.
[0070] According to a third aspect of the present invention, there is also provided an electrode plate for a lithium iron phosphate battery, comprising a current collector and an electrode material layer formed on a surface of the current collector, wherein the electrode material layer is made of the electrode slurry of the lithium iron phosphate battery.
[0071] In view of the advantages of the electrode material of the lithium iron phosphate battery mentioned above, the electrode plate made therefrom also has the same advantages.
[0072] According to a fourth aspect of the present invention, there is also provided a method for preparing an electrode sheet of a lithium iron phosphate battery, comprising the following steps:
[0073] Mixing an electrode active material, a binder, a conductive agent and a solvent to obtain a lithium iron phosphate electrode slurry;
[0074] The lithium iron phosphate electrode slurry is coated on the current collector to obtain an electrode plate.
[0075] The preparation method has simple operation and stable process and is suitable for large-scale industrial production.
[0076] In order to further illustrate the preparation method of the electrode sheet, the preparation methods of the positive electrode sheet and the negative electrode sheet are respectively described as examples.
[0077] As an optional embodiment of the present invention, a method for preparing a positive electrode sheet of a lithium iron phosphate battery comprises the following steps:
[0078] (a) mixing and stirring a binder with a portion of a solvent (NMP) to obtain a glue solution having a solid content of 4.5-5.5%;
[0079] (b) mixing the electrode active material (nanoscale spherical lithium iron phosphate material) and the conductive agent (molybdenum carbide) and dry mixing for 0.5-1h;
[0080] (c) adding the remaining amount of solvent (NMP), stirring for 1-2 hours to knead, and then adding a certain amount of conductive agent (CNT) and glue solution to stir, and finally obtaining a positive electrode slurry with a solid content of 62.5-65.5%;
[0081] (d) The positive electrode slurry is uniformly coated on the current collector (carbon-coated aluminum foil) by extrusion coating to obtain a positive electrode sheet.
[0082] As an optional embodiment of the present invention, a method for preparing a negative electrode sheet of a lithium iron phosphate battery comprises the following steps:
[0083] (a) mixing a binder (CMC) with a portion of a solvent (deionized water) to obtain a glue solution having a solid content of 1.5-2.5%;
[0084] (b) mixing the electrode active material (graphite) and the conductive agent (molybdenum carbide) and dry mixing for 0.5-1h;
[0085] (c) adding the remaining amount of solvent (NMP), stirring for 1-2 hours to knead, and then adding a certain amount of binder (SBR) and glue solution and stirring, finally obtaining a negative electrode slurry with a solid content of 51.5-54.5%;
[0086] (d) The negative electrode slurry is uniformly coated on the current collector (plain copper foil) by extrusion coating to obtain a negative electrode sheet.
[0087] According to a fifth aspect of the present invention, there is also provided a lithium iron phosphate battery, comprising the electrode material of the lithium iron phosphate battery or the electrode plate of the lithium iron phosphate battery.
[0088] In view of the advantages of the above-mentioned electrode materials or electrode plates, the lithium iron phosphate battery containing them has a higher energy density and good rate performance at low temperatures, meeting the usage requirements of more application scenarios.
[0089] The present invention is further described in detail below in conjunction with specific examples and comparative examples. It should be noted that the CNTs used in the following examples and comparative examples were purchased from Xiamen Kaina Graphene Technology Co., Ltd., with a CNT brand of KNG-C1411; SP was purchased from Huiping New Energy, with a brand of Super P Li; and graphite was purchased from Shanshan New Energy Co., Ltd., with a graphite particle size D50 of 14.5±2μm.
[0090] Example 1
[0091] This embodiment provides an electrode material (positive electrode material) for a lithium iron phosphate battery, comprising the following raw materials in the following mass fractions: 97% electrode active material, 1.5% binder and 1.5% conductive agent;
[0092] Among them, the electrode active material is spherical lithium iron phosphate with a particle size of 0.8-1.6μm; the binder is PVDF-HSV900 powder; the conductive agent includes molybdenum carbide and CNT, and the mass ratio of molybdenum carbide to CNT is 1:0.5, that is, the mass fraction of molybdenum carbide is 1%, and the mass fraction of CNT is 0.5%.
[0093] The preparation method of molybdenum carbide comprises the following steps:
[0094] (1) Dissolve 100 g of ammonium molybdate and 100 g of sucrose in 200 mL of deionized water, respectively, and then mix to obtain a uniform suspension;
[0095] (2) subjecting the suspension obtained in (1) to a hydrothermal reaction at 180° C. for 12 h;
[0096] (3) centrifuging the product after the hydrothermal reaction in (2), washing the separated solid product with deionized water three times and drying it at 60° C. for 12 h to obtain an intermediate product;
[0097] (4) The intermediate product obtained in (3) was calcined at 800° C. for 4 h under the protection of argon to obtain molybdenum carbide powder.
[0098] Example 2
[0099] This embodiment provides an electrode material (positive electrode material) for a lithium iron phosphate battery, comprising the following raw materials in the following mass fractions: 97% electrode active material, 1.5% binder and 1.5% conductive agent;
[0100] Among them, the electrode active material is spherical lithium iron phosphate with a particle size of 0.8-1.6 μm; the binder is PVDF-HSV900 powder; the conductive agent includes molybdenum carbide, SP and CNT, the mass ratio of molybdenum carbide, SP and CNT is 0.5:0.5:0.5, and the preparation method of molybdenum carbide is the same as that in Example 1.
[0101] Example 3
[0102] This embodiment provides an electrode material (positive electrode material) for a lithium iron phosphate battery, except that the conductive agent does not include CNT, that is, the conductive agent is only molybdenum carbide, and the total amount of the conductive agent remains unchanged at 1.5%. The types and amounts of other raw materials and the preparation method of molybdenum carbide are the same as those in Example 1.
[0103] Example 4
[0104] This embodiment provides an electrode material (positive electrode material) for a lithium iron phosphate battery, comprising the following raw materials in the following mass fractions: 97.5% electrode active material, 1.5% binder and 1% conductive agent;
[0105] The electrode active material is spherical lithium iron phosphate with a particle size of 0.8-1.6 μm; the binder is PVDF; the conductive agent is molybdenum carbide, and the preparation method of molybdenum carbide is the same as that of Example 1.
[0106] Example 5
[0107] This embodiment provides an electrode slurry (positive electrode slurry) for a lithium iron phosphate battery, including the positive electrode material for the lithium iron phosphate battery provided in Example 1 and solvent NMP, and the mass ratio of the positive electrode material to the solvent NMP is 63:37.
[0108] The method for preparing the electrode slurry (positive electrode slurry) of the lithium iron phosphate battery of this embodiment comprises the following steps:
[0109] (a) mixing the binder PVDF-HSV900 powder and a portion of NMP (accounting for 5% of the total amount of NMP) to obtain a glue solution with a solid content of 5±0.5%;
[0110] (b) mixing spherical lithium iron phosphate and molybdenum carbide, and dry mixing at high speed (speed of 2000 rpm) for 0.5 h;
[0111] (c) adding the remaining NMP, stirring at a low speed (rotation speed of 800 rpm) for 1 h to knead, and then adding CNT and glue solution and stirring at a high speed (rotation speed of 800 rpm) to obtain a positive electrode slurry with a solid content of 63±1.5%.
[0112] Example 6-Example 8
[0113] Examples 6-8 respectively provide an electrode slurry (positive electrode slurry) for a lithium iron phosphate battery, which respectively include the positive electrode material for the lithium iron phosphate battery provided in Examples 2-4 and solvent NMP, and the mass ratio of the positive electrode material to the solvent NMP is 63:37.
[0114] The preparation method of the electrode slurry (positive electrode slurry) of the lithium iron phosphate battery of Example 6-Example 8 is the same as that of Example 5.
[0115] Example 9
[0116] The present embodiment provides an electrode plate (positive electrode plate) of a lithium iron phosphate battery, including a current collector and an electrode material layer formed on the surface of the current collector. The electrode material layer is made of the electrode slurry (positive electrode slurry) of the lithium iron phosphate battery provided in Example 5. The thickness of the electrode material layer is 170 μm. The current collector is a carbon-coated aluminum foil with a thickness of 12 μm.
[0117] The method for preparing the electrode plate (positive electrode plate) of the lithium iron phosphate battery of this embodiment comprises the following steps:
[0118] The electrode slurry (positive electrode slurry) was uniformly coated on the carbon-coated aluminum foil by extrusion coating to obtain a surface density of 380 g / m 2 Electrode plate (positive electrode plate).
[0119] Example 10-Example 12
[0120] Examples 10-12 respectively provide an electrode plate (positive electrode plate) for a lithium iron phosphate battery. Except that the electrode material layer is made of the electrode slurry (positive electrode slurry) for the lithium iron phosphate battery provided by Examples 6-8, the rest of the composition and preparation method are the same as those of Example 9.
[0121] Example 13
[0122] This embodiment provides a lithium iron phosphate battery, including the electrode plate (positive electrode plate) and negative electrode plate of the lithium iron phosphate battery provided in Example 9;
[0123] The negative electrode plate includes a current collector and a negative electrode material layer formed on the surface of the current collector. The current collector is copper foil with a thickness of 6 μm. The negative electrode material layer is made of negative electrode slurry, and the thickness of the negative electrode material layer is 125 μm.
[0124] The negative electrode slurry includes negative electrode material and solvent (deionized water), and the mass ratio of negative electrode material to solvent is 52:48. Taking the mass fraction of negative electrode material as 100%, the negative electrode material includes the following raw materials in mass fractions:
[0125] Electrode active material 96.5%, binder 2.5% and conductive agent 1.0%;
[0126] The electrode active material is graphite with a particle size of 12-15 nm; the binder includes CMC-2200 and SBR, and the mass ratio of CMC-2200 to SBR is 0.5:2.0; and the conductive agent is molybdenum carbide.
[0127] The method for preparing the negative electrode sheet comprises the following steps:
[0128] (1) Mixing CMC-2200 powder and a portion of deionized water (accounting for 2% of the total amount of deionized water) to obtain a glue solution with a solid content of 2±0.5%;
[0129] (2) Mixing graphite and molybdenum carbide, and dry mixing at high speed (speed of 2000 rpm) for 0.5 h;
[0130] (3) Add the remaining amount of deionized water, stir at a low speed (speed of 800 rpm) for 1 h to knead, then add SBR and glue solution and stir at a high speed (speed of 800 rpm) to obtain a negative electrode slurry with a solid content of 53±1.5%;
[0131] (4) The above slurry was evenly coated on the bare copper foil by extrusion coating to obtain a surface density of 172 g / m 2 The negative electrode.
[0132] The assembly method of the lithium iron phosphate battery is as follows: the positive electrode sheet and the negative electrode sheet are rolled and die-cut, and then wound to form a winding core, and then the connecting sheet and the cover plate are welded and then baked. After liquid injection, the lithium ion battery with a capacity of 168Ah is obtained after high-temperature standing, formation, and capacity division.
[0133] Embodiment 14
[0134] This embodiment provides a lithium iron phosphate battery, including the electrode plate (positive electrode plate) and negative electrode plate of the lithium iron phosphate battery provided in Example 10;
[0135] The conductive agent used in the negative electrode plate includes molybdenum carbide and SP, the mass ratio of molybdenum carbide to SP is 1:1, the total amount of the conductive agent remains unchanged, and the composition, amount and preparation method of the other raw materials are the same as Example 13.
[0136] Embodiment 15
[0137] This embodiment provides a lithium iron phosphate battery, including the electrode plate (positive electrode plate) and negative electrode plate of the lithium iron phosphate battery provided in Example 11;
[0138] The composition and preparation method of the negative electrode plate, and the assembly method of the lithium iron phosphate battery are the same as those in Example 13.
[0139] Example 16
[0140] This embodiment provides a lithium iron phosphate battery, including the electrode plate (positive electrode plate) and negative electrode plate of the lithium iron phosphate battery provided in Example 12;
[0141] The composition and preparation method of the negative electrode plate, and the assembly method of the lithium iron phosphate battery are the same as those in Example 13.
[0142] Comparative Example 1
[0143] This comparative example provides an electrode material (positive electrode material) for a lithium iron phosphate battery. Except that the molybdenum carbide in the conductive agent is replaced with an equal amount of SP, the rest of the composition and amount are the same as those in Example 1.
[0144] Comparative Example 2
[0145] This comparative example provides an electrode slurry (positive electrode slurry) for a lithium iron phosphate battery. Except for using the electrode material (positive electrode material) for the lithium iron phosphate battery provided in comparative example 1, the remaining raw materials and amounts are the same as those in example 5.
[0146] The preparation method of the electrode slurry (positive electrode slurry) of the lithium iron phosphate battery in this comparative example is the same as that in Example 5, except that the molybdenum carbide in step (b) is replaced by SP. The remaining steps and process parameters are the same as those in Example 5.
[0147] Comparative Example 3
[0148] This comparative example provides an electrode plate (positive electrode plate) for a lithium iron phosphate battery. Except for using the electrode slurry (positive electrode slurry) for the lithium iron phosphate battery provided in comparative example 2, the remaining raw materials, amounts and preparation methods are the same as those in Example 9.
[0149] Comparative Example 4
[0150] This comparative example provides a lithium iron phosphate battery, including the electrode plate (positive electrode plate) and negative electrode plate of the lithium iron phosphate battery provided in comparative example 3;
[0151] The conductive agent used in the negative electrode plate was replaced by an equal amount of SP from molybdenum carbide, and the remaining raw materials, amounts and preparation methods were the same as those in Example 13.
[0152] Comparative Example 5
[0153] This comparative example provides a lithium iron phosphate battery, except that the preparation method of the positive electrode plate is different from that of the positive electrode plate in Example 13, the rest of the structure and preparation method are the same as those in Example 13;
[0154] The method for preparing the positive electrode sheet comprises the following steps:
[0155] (a) Preparation of coated aluminum foil:
[0156] Molybdenum carbide and polyacrylonitrile are ground and mixed in a mass ratio of 1:1, and nitrogen methyl pyrrolidone is added and dispersed to obtain a conductive coating slurry;
[0157] The aluminum foil is subjected to plasma surface treatment by plasma equipment, and the conductive coating slurry is coated on both sides of the aluminum foil subjected to plasma surface treatment. The thickness of the conductive coating on one side is 0.5 μm, and the surface density is 1.2 g / m 2 , heating to 400°C at 3°C / min, heat treating for 4h, and cooling to room temperature to obtain coated aluminum foil;
[0158] (b) The electrode slurry (positive electrode slurry) provided in Comparative Example 2 was uniformly coated on the above-mentioned coated aluminum foil by extrusion coating to obtain a surface density of 380 g / m 2 The electrode sheet (positive electrode sheet) has a thickness of the positive electrode material layer of 169.5 μm.
[0159] In order to compare the technical effects of the above embodiments and comparative examples, the following experimental examples are specially designed.
[0160] Experimental Example 1
[0161] The electrochemical properties of the lithium iron phosphate batteries provided in Examples 13 to 16 and Comparative Examples 4 to 5 were tested.
[0162] Specifically, the lithium iron phosphate batteries provided in the embodiments and comparative examples were subjected to a 10s (10 seconds) discharge DCR test at 30% SOC, 50% SOC and 70% SOC at 25°C, as shown in Tables 1 and Figure 1 shown.
[0163] The lithium iron phosphate batteries provided in the embodiments and comparative examples were tested for discharge capacity at different rates at 25°C, as shown in Table 2 and Figure 2 shown.
[0164] At the same time, the discharge capacity of the lithium iron phosphate batteries provided in the embodiments and comparative examples at 1C at -20°C was tested. See Table 3 and Figure 3 shown.
[0165] Table 1
[0166]
[0167] Table 2
[0168]
[0169] Table 3
[0170]
[0171]
[0172] From Table 1 and Figure 1 It can be seen that the DCR of the lithium iron phosphate battery provided in the embodiment of the present invention at different SOCs is generally lower than the DCR of the lithium iron phosphate battery of the comparative example, and among the embodiments, the DCR of embodiment 13 at different SOCs is the smallest.
[0173] From Table 2 and Figure 2 It can be seen that the rate performance of the lithium iron phosphate battery provided by the embodiments of the present invention is generally better than that of the comparative example, and among the embodiments, embodiment 13 shows better rate performance.
[0174] From Table 3 and Figure 3 It can be seen that, relative to the lithium iron phosphate battery provided in the comparative example, the lithium iron phosphate batteries provided in each embodiment of the present invention have a higher discharge capacity, and the discharge capacity of Example 13 at -20°C is the highest.
[0175] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. An electrode material for a lithium iron phosphate battery, characterized in that: Taking the mass fraction of electrode material as 100%, the components include the following mass fractions: Electrode active material 96-98%, binder 1.5-2.5% and conductive agent 0.5-1.5%; Wherein, the conductive agent includes molybdenum carbide.
2. The electrode material for lithium iron phosphate battery according to claim 1, characterized in that: The particle size of the molybdenum carbide is D50=0.5-1.3 μm; And / or, the conductive agent further includes at least one of carbon nanotubes, SP or acetylene black.
3. The electrode material for lithium iron phosphate battery according to claim 1, characterized in that: The preparation method of molybdenum carbide comprises the following steps: The ammonium molybdate and the carbon source are mixed to carry out a hydrothermal reaction, and after the reaction is completed, the obtained reaction product is separated into a solid and a liquid, and dried to obtain an intermediate product; The intermediate product is calcined under a protective atmosphere to obtain molybdenum carbide.
4. The electrode material for lithium iron phosphate battery according to claim 3, characterized in that: The carbon source includes at least one of sucrose, glucose or fructose; And / or, the mass ratio of the ammonium molybdate to the carbon source is 1:(1-1.03); And / or, the temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 10-14 h; And / or, the drying temperature is 50-70°C and the drying time is 10-14h; And / or, the calcination temperature is 750-850° C., and the calcination time is 4-6 hours.
5. The electrode material for lithium iron phosphate battery according to any one of claims 1 to 4, characterized in that: When the electrode material is a positive electrode material, the electrode active material includes a lithium iron phosphate active material, and / or the binder includes PVDF.
6. The electrode material for lithium iron phosphate battery according to any one of claims 1 to 4, characterized in that: When the electrode material is a negative electrode material, the negative electrode active material includes graphite, and / or the binder includes carboxymethyl cellulose and / or styrene-butadiene rubber.
7. An electrode slurry for a lithium iron phosphate battery, characterized in that: An electrode material for a lithium iron phosphate battery comprising any one of claims 1 to 6 and a solvent; The solvent includes N-methylpyrrolidone and / or water.
8. An electrode plate for a lithium iron phosphate battery, characterized in that: It comprises a current collector and an electrode material layer formed on the surface of the current collector, wherein the electrode material layer is made of the electrode material of the lithium iron phosphate battery according to any one of claims 1 to 6 or the electrode slurry of the lithium iron phosphate battery according to claim 7.
9. The method for preparing an electrode sheet of a lithium iron phosphate battery according to claim 8, characterized in that: The following steps are involved: Mixing an electrode active material, a binder, a conductive agent and a solvent to obtain a lithium iron phosphate electrode slurry; The lithium iron phosphate electrode slurry is coated on the current collector, and then dried and rolled to obtain the electrode plate.
10. A lithium iron phosphate battery, characterized in that: An electrode material for a lithium iron phosphate battery comprising any one of claims 1 to 6 or an electrode plate for a lithium iron phosphate battery according to claim 8.
Citation Information
Patent Citations
Lithium iron phosphate positive pole piece and preparation method and application thereof
CN113422049A